Comparative Historical Analysis of Alor Languages: Toward Proto-Alor-Pantar Reconstruction - Salimulloh Tegar Sanubarianto (Southeast Asian Language and Literature Studies, 2025)
This study aims to examine the degree of kinship among the Kui, Hamap, and Kamang languages spoken in Alor Regency, East Nusa Tenggara Province. The investigation employs a comparative historical linguistic approach and the lexicostatistical method using 200 Swadesh basic vocabulary items. Data were collected through interviews with native speakers and subsequently analyzed to identify cognate vocabulary, calculate the percentage of cognacy, and construct a kinship tree diagram. The findings reveal that the degree of kinship between the Kui and Hamap languages is 18.5%, between Kui and Kamang is 14%, and between Hamap and Kamang is 12%. Based on the lexicostatistical categories, these three languages belong to the same stock, yet exhibit a low degree of kinship. This finding indicates that although the three languages are geographically spoken in neighboring areas, their kinship relations are relatively distant. This study constitutes an initial step toward the reconstruction of a proto-language in Alor Regency and contributes to the classification of the languages in East Nusa Tenggara.